2022
DOI: 10.1371/journal.pone.0263684
|View full text |Cite
|
Sign up to set email alerts
|

The human ACE-2 receptor binding domain of SARS-CoV-2 express on the viral surface of the Newcastle disease virus as a non-replicating viral vector vaccine candidate

Abstract: Since the SARS-CoV-2 infection was identified in December 2019, SARS-CoV-2 infection has rapidly spread worldwide and has become a significant pandemic disease. In addition, human death and serious health problem caused by SARS-CoV-2 infection, the socio-economic impact has been very serious. Here, we describe the development of the viral vector vaccine, which is the receptor-binding domain (RBD) of SARS-CoV-2 expressed on the surface of Newcastle disease virus (LVP-K1-RBD19). The RBD protein concentrations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The previously generated full-length cDNA clone of recombinant NDV (rNDV), which contained the transgene cassette inserted between the NP and P genes of the non-pathogenic NDV VG/GA strain), was used as the backbone to construct new cDNA. 22,36 The plasmid was linearized by restriction enzyme digestion to allow insertion of the extracellular form of the human TRAIL gene (amino acids 114-281). The TRAIL gene was amplified with NotI-GE-IG-GS-Kozak at the 3′-end and FseI at the 5′-end using the Phusion Flash High-Fidelity PCR Master Mix (cat.…”
Section: Cdna Construction Of Ndv Containing Trail Genementioning
confidence: 99%
“…The previously generated full-length cDNA clone of recombinant NDV (rNDV), which contained the transgene cassette inserted between the NP and P genes of the non-pathogenic NDV VG/GA strain), was used as the backbone to construct new cDNA. 22,36 The plasmid was linearized by restriction enzyme digestion to allow insertion of the extracellular form of the human TRAIL gene (amino acids 114-281). The TRAIL gene was amplified with NotI-GE-IG-GS-Kozak at the 3′-end and FseI at the 5′-end using the Phusion Flash High-Fidelity PCR Master Mix (cat.…”
Section: Cdna Construction Of Ndv Containing Trail Genementioning
confidence: 99%
“…Combinations of intranasal and intramuscular doses have also been assessed for several vaccine candidates [ 30 , 31 , 70 , 76 ]. Inactivated NDV-vectored vaccines, on the other hand, have been administered exclusively by the intramuscular route, as the inactivated virus can no longer replicate in the mucosal passages [ 31 , 75 , 76 , 78 ].…”
Section: Ndv-vectored Vaccinesmentioning
confidence: 99%
“…NDV-vectored vaccines have great potential to be used against pandemic diseases, having shown efficient protection against EBOV [ 13 , 29 , 77 ], SARS-CoV [ 28 ] and SARS-CoV-2 [ 18 , 26 , 27 , 30 , 31 , 75 , 76 , 78 ]. Intranasal vaccines against EBOV have been shown to induce neutralizing antibody responses in monkeys [ 29 ], guinea pigs [ 13 ] and mice [ 77 ], although the latter study found more robust responses when mixing adenovirus and NDV-vectored doses as compared to a homologous NDV-vectored regimen.…”
Section: Ndv-vectored Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the coinfection with influenza and SARS-CoV-2 can substantially increase fatality rates, particularly among the high-risk populations such as the elderly and immunocompromised patients. 3 Therefore, it is vital to assess the threats associated with the coexistence of influenza and SARS-CoV-2. So, in the following sections, we will focus on the risks and threats related to the Florona.…”
Section: Dear Editormentioning
confidence: 99%